Belief in God in an age of science - Polkinghorne, J. C., 1930-2021 (Yale University Press, 1998)
In this book, the author focuses on the collegiality between science and theology, contending that these "intellectual cousins" are both concerned with interpreted experience and with the quest for truth about reality. He argues eloquently that scientific and theological enquiries are parallel.
The first four chapters are based on the Terry Lectures, which the author gave at Yale University in Oct. 1996.
Keywords: Religion and science.; Religion and Science; Religion et sciences.; RELIGION -- Christianity -- General.; RELIGION -- Christian Life -- Social Issues.; Religion and science